Visualization of bone marrow monocyte mobilization using Cx3cr1gfp/+Flt3L−/− reporter mouse by multiphoton intravital microscopy. Issue 3 (16th December 2014) - Evrard, Maximilien; Chong, Shu Zhen; Devi, Sapna; Chew, Weng Keong; Lee, Bernett; Poidinger, Michael; Ginhoux, Florent; Tan, Suet Mien; Ng, Lai Guan
Abstract : A new approach that monitors monocyte mobilization from the bone marrow to the bloodstream as a complement to cell population-based techniques. Abstract: Monocytes are innate immune cells that play critical roles in inflammation and immune defense. A better comprehension of how monocytes are mobilized and recruited is fundamental to understand their biologic role in disease and steady state. The BM represents a major "checkpoint" for monocyte homeostasis, as it is the primary site for their production and release. Our study determined that the Cx3cr1 gfp/+ mouse strain is currently the most ideal model for the visualization of monocyte behavior in the BM by multiphoton intravital microscopy. However, we observed that DCs are also labeled with high levels of GFP and thus, interfere with the accuracy of monocyte tracking in vivo. Hence, we generated a Cx3cr1 gfp/+ Flt3L −/− reporter mouse and showed that whereas monocyte numbers were not affected, DC numbers were reduced significantly, as DCs but not monocytes depend on Flt3 signaling for their development. We thus verified that mobilization of monocytes from the BM in Cx3cr1 gfp/+ Flt3L −/− mice is intact in response to LPS. Collectively, our study demonstrates that the Cx3cr1 gfp/+ Flt3L −/− reporter mouse model represents a powerful tool to visualize monocyte activities in BM and illustrates the potential of a Cx3cr1 gfp/+ -based, multifunctionality fluorescence reporter approach to dissect monocyte function in vivo.